Spectrophotometric assessment of peri‐implant mucosa after restoration with zirconia abutments veneered with fluorescent ceramic: a controlled, retrospective clinical study. (6th December 2011) - Happe, Arndt; Schulte‐Mattler, Verena; Fickl, Stefan; Naumann, Michael; Zöller, Joachim E; Rothamel, Daniel
Abstract: Objectives: The purpose of this study was to investigate the optical appearance of the soft tissue labial to dental implants restored with fluorescent ceramic‐veneered zircona abutments. It was hypothesized that the tested abutment design leads to an increased brightness in the marginal peri‐implant tissue, which does not differ from that of natural teeth. Moreover, a reduction of the color difference that has been reported from other abutment materials was expected. Materials and methods: A total of 12 patients with single titanium implants in the maxillary anterior region were recruited. All implants ( N  = 12) were restored with zirconia abutments veneered with fluorescent ceramic and full‐ceramic crowns. Color measurements of the peri‐implant mucosa at the test sites were made of the facial aspect of the teeth using a Spectroshade‐spectrophotometer. The gingiva of a contralateral or adjacent natural tooth served as a control. Color data (CIE‐ L*a*b* color coordinates) were obtained in five incremental areas of 1 × 2 mm in both test and control sites. ∆E ‐values were calculated from the ΔL*, Δa* and Δb* values for each patient. Results: Data acquisition from the test site demonstrated lower mean values of L*, a* and b* than the control site. Statistical significance between the test site and control site was reached in the L* values only in the second of the five incremental areas ( P  < 0.05, Wilcoxon test). However, discrepancies in a*‐ and b*‐ values reached a statistically significant difference in the incremental areas 1, 2 and 4, and in b * in area 5 ( P  < 0.05, Wilcoxon test). Medians of the ∆E ‐values in all five increments were found to be higher than the clinical perceptual threshold of 3.7. However, considering the original data, five individual patients did not reach the threshold in increment 1 and 2, two in increment 3 and three in increment 4. None of the patients showed lower ∆E ‐values than the perceptual threshold of 3.7 in increment 5, which had the largest distance from the gingival margin. Conclusion: The tested abutment design leads to a peri‐implant soft tissue color that, in the critical marginal area, in five of 12 patients did not statistically differ from the tissue of the gingiva of natural teeth. Particularly, the brightness of the peri‐implant soft‐tissue seemed to be more adapted to the natural situation using a fluorescent abutment design.